COP26 and a Framework for Future Global Agreements on Carbon Market Integrity. Issue 1 (1st June 2022) - Cadman, Tim; Hales, Robert
Abstract: The international political economy is developing carbon markets based on decisions made in Glasgow in 2021 at COP26. The development of such markets is problematic. An examination of the history of the agreements made at the climate change conferences indicates issues that remain pertinent today. These include the ability of markets to provide the necessary reductions in fossil fuel emissions at a scale large enough to combat climate change; the integrity of current systems for the accounting of carbon; possible negative impacts on natural capital generally and biodiversity in particular arising from such mechanisms; the inherent risks associated with trying to simultaneously deliver other (co-)benefits; and clarity over the extent to which the rights will be safeguarded. While there is an urgency in ensuring that mechanisms will deliver the emissions reductions required, the risks of carbon market failure remain due to the insufficiency of Nationally Determined Contributions (NDCs) and the lack of transparency of carbon markets. Integrity systems based on sound principles for governing the integrity of carbon offsets and other mechanisms to reduce emissions are required. Unless standards are adopted, the likelihood of combatting climate change effectively, in the context of the danger of greenwashing and the ongoing pandemic, remains uncertain.